Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1128/jvi.02956-12
|View full text |Cite
|
Sign up to set email alerts
|

Insights into a Viral Lytic Pathway from an Archaeal Virus-Host System

Abstract: c Archaeal host cells infected by Sulfolobus turreted icosahedral virus (STIV) and Sulfolobus islandicus rod-shaped virus 2 (SIRV2) produce unusual pyramid-like structures on the cell surface prior to virus-induced cell lysis. This viral lysis process is distinct from known viral lysis processes associated with bacterial or eukaryal viruses. The STIV protein C92 and the SIRV2 protein 98 are the only viral proteins required for the formation of the pyramid lysis structures of STIV and SIRV2, respectively. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Perhaps one of the best studied archaeal virus-host systems is the STIV-Sulfolobus model system (Brumfield et al, 2009;Dellas et al, in preparation;Fu and Johnson, 2012;Fu et al, 2010;Khayat et al, 2010Khayat et al, , 2005Larson et al, 2007aLarson et al, , 2007bLarson et al, , 2006Maaty et al, 2006Maaty et al, , 2012Ortmann et al, 2008;Rice et al, 2004;Snyder et al, 2011aSnyder et al, , 2011bSnyder et al, , 2013aSnyder et al, , 2013bVeesler et al, 2013;Wirth et al, 2011). Even though a complete archaeal virus replication cycle has not been solved, several steps of the STIV replication cycle have been described (Brumfield et al, 2009;Dellas et al, in preparation;Fu et al, 2010;Happonen et al, 2013;Snyder et al, 2011bSnyder et al, , 2013b.…”
Section: Archaeal Virus-host Model Systemsmentioning
confidence: 94%
“…Perhaps one of the best studied archaeal virus-host systems is the STIV-Sulfolobus model system (Brumfield et al, 2009;Dellas et al, in preparation;Fu and Johnson, 2012;Fu et al, 2010;Khayat et al, 2010Khayat et al, , 2005Larson et al, 2007aLarson et al, , 2007bLarson et al, , 2006Maaty et al, 2006Maaty et al, , 2012Ortmann et al, 2008;Rice et al, 2004;Snyder et al, 2011aSnyder et al, , 2011bSnyder et al, , 2013aSnyder et al, , 2013bVeesler et al, 2013;Wirth et al, 2011). Even though a complete archaeal virus replication cycle has not been solved, several steps of the STIV replication cycle have been described (Brumfield et al, 2009;Dellas et al, in preparation;Fu et al, 2010;Happonen et al, 2013;Snyder et al, 2011bSnyder et al, , 2013b.…”
Section: Archaeal Virus-host Model Systemsmentioning
confidence: 94%
“…For example, VAP opening may be dependent on the specific growth conditions (temperature and pH). However, it is also possible that the opening mechanism is directly controlled by a factor encoded by the virions themselves, as they are dependent on the precise timing of VAP opening to avoid the release of immature virions Snyder et al 2013a;Daum et al 2014). …”
Section: Vap Assembly and Openingmentioning
confidence: 99%
“…Expression of STIV1-and SIRV2-based PVAP chimeras in the STIV1 infection system showed that both proteins and all chimeras resulted in the formation of VAPs of the same size and geometry (Snyder et al 2013a). However, neither the chimeras nor SIRV2_PVAP were sufficient to support STIV1 infection, suggesting that the two proteins are not completely interchangeable.…”
Section: Vap Diversitymentioning
confidence: 99%
“…Of the predicted 38 open reading frames encoded by STIV (including the more recently identified B129 [8]), 11 have been experimentally investigated through genetic knockout experiments (9), biochemical analysis (2, 10, 11), or structural characterization (5)(6)(7)(12)(13)(14). While certain steps of the STIV infection cycle are under investigation (11,15), much remains to be understood, including the processes of viral attachment and viral DNA packaging.STIV B204 belongs to the FtsK/HerA superfamily (3), whose members share several conserved amino acid sequence motifs. In …”
mentioning
confidence: 99%